2019
DOI: 10.1186/s12935-019-0789-y
|View full text |Cite
|
Sign up to set email alerts
|

Lycopene improves the efficiency of anti-PD-1 therapy via activating IFN signaling of lung cancer cells

Abstract: BackgroundMonoclonal antibodies targeting programmed death-1 receptor (PD-1) and its ligand (PD-L1) have been developed to treat cancers including lung cancer. In this study, we aimed to investigate whether lycopene could promote the effect of anti-PD-1 treatment on lung cancer.MethodsTumor formation assay was conducted. Immune reactions were assessed by detecting several cytokine levels using enzyme-like immunosorbent assay. T cell activity was analyzed using cytometry. The mechanism of lycopene action was in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 41 publications
1
22
0
Order By: Relevance
“…There was a significant increment observed in IL-2, IFNγ, CD4 + :CD8 + T cells ratio, percentage of IFNγ + /CD8 + T cells, percentage of perforin + /CD8 + T cell, percentage of granzyme B + /CD8 + T cell, gene expression of IFNβ, IFNγ, IRF1, IRF7, CXCL9 and CXCL10. Similar to the in vitro study, no change was observed in gene expression of DNMT1, DNMT3b, IRF3 and IRF8 [69].…”
Section: Animal Studiessupporting
confidence: 80%
See 1 more Smart Citation
“…There was a significant increment observed in IL-2, IFNγ, CD4 + :CD8 + T cells ratio, percentage of IFNγ + /CD8 + T cells, percentage of perforin + /CD8 + T cell, percentage of granzyme B + /CD8 + T cell, gene expression of IFNβ, IFNγ, IRF1, IRF7, CXCL9 and CXCL10. Similar to the in vitro study, no change was observed in gene expression of DNMT1, DNMT3b, IRF3 and IRF8 [69].…”
Section: Animal Studiessupporting
confidence: 80%
“…In this experiment, lycopene managed to enhance IFNβ, IFNγ, IRF1, IRF7, CXCL9, CXCL10 while suppressing IL-4, IL-10, DMNT3a, methylation of IRF1, IRF7 promoters and most importantly, the tumor volume. Increment of CD4 + /CD8 + T cells ratio, percentage of IFNγ + /CD8 + T cell, percentage of perforin + /CD8 + T cell and percentage of granzyme B + /CD8 + T cell were reported, accompanied by no significant change in DNMT1 and DNMT3b [69]. Compiling these evidences depicted that lycopene could enhance activation and differentiation of T cells and T helper cells Th1/Th2 drift via suppression of IL-4 and upregulation of IFNγ, most probably by its ability to modulate cytokines, chemokines and interferons.…”
Section: Immunomodulatory Effects Of Lycopenementioning
confidence: 92%
“…IFN-γ is indispensable for anti-PD-1 treatment due to its role in the fragility of Tregs [49,50]. Increased IFN can improve the efficacy of anti-pd-1 therapy [51].…”
Section: Functional Status Of Immune Cells Is Related To Anti-tumor Imentioning
confidence: 99%
“…In 1997, Talwar et al presented the effect of inflammation on the content of antioxidants, among others, lycopene in patients with nonsmall cell lung cancer (NSCLC) (21). In in vivo studies on mice, Jiang et al tested the effect of lycopene on improving the effect of monoclonal antibody therapy (22). Sheriff et al performed studies in rats that examined the effect of lycopene in preventing mitochondrial dysfunction during d-GalN / LPS-induced FHF (23).…”
Section: Discussionmentioning
confidence: 99%